Hope and Hopelessness: Cardenal and Menen Desleal - Arias Ramírez, Luis Alejandro (2025)
The literary proposals during the Cold War in Central America were diverse and reflected ideological uncertainty at that time. In that context, the poetry collection, Salmos, by Ernesto Cardenal, and the short story, Hacer el amor en el refugio atómico, by Álvaro Menen Desleal, convey two different perspectives for the ethical concept of “hope.” These perspectives will be analyzed and described in this paper, seeking common features and relations to explain whether they both portray images of different realities, or perhaps two facets of the same context.